Global pandemics and epistemic crises in psychology : a socio-philosophical approach - Dege, Martin; Strasser, Irene, 1979- (New York : Routledge, 2021)
"Using COVID-19 as a base, this ground-breaking book brings together several renowned scholars to explore the concept of crisis, and how this global event has shaped the discipline of psychology. It engages directly with the challenges that psychology continues to face when theorizing societal issues of gender, race, class, history and culture, while not disregarding 'lived' experiences. This edited volume offers a set of pathways to rethink psychology beyond its current scope and history to become more apt to the conditions, needs, and demands of the 21st century. The book explores topics like resilience, interpersonal relationships, mistrust in the government and access to healthcare. Dividing the book into three distinct sections, the contributors first examine the current crisis within psychology, then go on to explore how psychology theorizes the subject and the other in a social world of perpetual political, economic, cultural, and social crises, and lastly consider the role of crises in the creation of new theorizing. This is essential reading for advanced undergraduate and postgraduate students of theoretical and philosophical psychology, social psychology, community psychology and developmental psychology"--
Keywords: Psychology; Psychology -- Philosophy; Social psychology; Developmental psychology; PSYCHOLOGY / General